Pharmacokinetic/Pharmacodynamic Optimization of Hospital-Acquired and Ventilator-Associated Pneumonia: Challenges and Strategies - Abouelhassan, Yasmeen P.; Nicolau, David (Seminars in Respiratory and Critical Care Medicine, 2022)
Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) are correlated with high mortality rates worldwide. Thus, the administration of antibiotic therapy with appropriate dosing regimen is critical. An efficient antibiotic is needed to maintain an adequate concentration at the infection site, for a sufficient period of time, to achieve the best therapeutic outcome. It can, however, be challenging for antibiotics to penetrate the pulmonary system due to the complexity of its structure. Crossing the blood alveolar barrier is a difficult process determined by multiple factors that are either drug related or infection related. Thus, the understanding of pharmacokinetics/pharmacodynamics (PK/PD) of antibiotics identifies the optimum dosing regimens to achieve drug penetration into the epithelial lining fluid at adequate therapeutic concentrations. Critically ill patients in the ICU can express augmented renal clearance (ARC), characterized by enhanced renal function, or may have renal dysfunction necessitating supportive care such as continuous renal replacement therapy (CRRT). Both ARC and CRRT can alter drug elimination, thus affecting drug concentrations. PK of critically ill patients is less clear due to the multiple variabilities associated with their condition. Therefore, conventional dosing regimens often lead to therapeutic failure. Another major hurdle faced in optimizing treatment for HAP/VAP is the reduction of the in vitro potency. Therapeutic drug monitoring (TDM), if available, may allow health care providers to personalize treatment to maximize efficacy of the drug exposures while minimizing toxicity. TDM can be of significant importance in populations whom PK are less defined and for resistant infections to achieve the best therapeutic outcome.
Keywords: nosocomial pneumonia; pharmacokinetics/pharmacodynamics; drug optimization; augmented renal clearance; continuous renal replacement therapy; antibiotic resistance; therapeutic drug monitoring